Complications of epidural adhesiolysis - Fishchenko, Iakiv; Piontkovskyi, Valentyn; Zlativ, Volodimir (Journal of Education, Health and Sport, 2016)
Fishchenko Iakiv, Piontkovskyi Valentyn, Zlativ Volodimir. Complications of epidural adhesiolysis. Journal of Education, Health and Sport. 2016;6(2):183-189. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46408 http://ojs.ukw.edu.pl/index.php/johs/article/view/3384 https://pbn.nauka.gov.pl/works/716072 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016. Complications of epidural adhesiolysis Iakiv Fishchenko SI "Institute of traumatology and orthopedics NAMS of Ukraine" Valentyn Piontkovskyi Rivne rigional hospital Ukraine Volodimir Zlativ Rivne rigional hospital, Ukraine Complications of epidural adhesiolysis Epidural adhesiolysis is a minimally invasive procedure used to treat neuro-compression pain of the lumbosacral part of spine with degenerative diseases. Thanks to being minimally invasive and to its high efficiency, the rate of this procedure in recent years has increased significantly. On a material of 760 patients we analyzed the mistakes and complications related to epidural adhesiolysis. The complications of varying severity were observed in our 297 (30.0%) patients. Of these, the complications which did not require any modifications of treatment strategies, or its minor correction occurred in 277 (36.4%) patients; complications requiring reinstallation of the catheter were observed in 15 (1.9%) patients; complications of moderate severity, as epidural hematoma, epiduritis we noted in 5 (0.6%) patients; threatening complication of spontaneous rupture of the dura mater followed by the catheter hypertonic solution of sodium chloride, we observed in one (0.1%) case. Key words: epidural adhesiolysis, neuro-compression pain, complications.